2013
DOI: 10.1038/hr.2013.119
|View full text |Cite
|
Sign up to set email alerts
|

Telmisartan delays myocardial fibrosis in rats with hypertensive left ventricular hypertrophy by TGF-β1/Smad signal pathway

Abstract: Hypertensive myocardial remodeling has an important role in the pathophysiology of hypertensive disease. This study suggests that telmisartan (TEL) can inhibit myocardial fibrosis of hypertensive left ventricular hypertrophy (LVH) through the transforming growth factor-β1 (TGF-β1)/Smad signaling pathway. Through echocardiography and hemodynamics, it was shown that TEL could improve cardiac function and reduce the degree of hypertensive LVH in hypertensive rats. Through immunoassay, it was shown that TEL could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 26 publications
1
40
0
1
Order By: Relevance
“…Further, blockade of angiotensin II type I receptor (AT 1 ), or downregulation of AT 1, has been shown to inhibit the activation of multiple pro-fibrotic pathways in heart and kidney. [19][20][21] We have previously reported that chronic infusion of Ang-II induces IL-18 and MMP9 expression in hypertrophied mouse myocardium, but suppresses RECK expression. 22 Analogous results were obtained in cultured CF.…”
Section: Introductionmentioning
confidence: 98%
“…Further, blockade of angiotensin II type I receptor (AT 1 ), or downregulation of AT 1, has been shown to inhibit the activation of multiple pro-fibrotic pathways in heart and kidney. [19][20][21] We have previously reported that chronic infusion of Ang-II induces IL-18 and MMP9 expression in hypertrophied mouse myocardium, but suppresses RECK expression. 22 Analogous results were obtained in cultured CF.…”
Section: Introductionmentioning
confidence: 98%
“…Fat redistribution induced by PPAR-γ agonists is characterized by the differentiation of pre-adipocytes into small fat cells in subcutaneous fat depots and apoptosis of differentiated large adipocytes in visceral fat depots54 . In animal studies, telmisartan reduced adipocyte size and protected against obesity and steatohepatitis compared to valsartan55 , furthermore, showed cardio-protective effect in rats with hypertensive left ventricular hypertrophy56 . This change in fat distribution could explain the favorable effects of telmisartan on reducing pro-inflammatory cytokines, like IL-6 and TNF-α levels, and increasing adiponectin levels.…”
mentioning
confidence: 99%
“…11,12 Because LVH is related to many forms of heart disease, experimental models of myocardial hypertrophy constitute an important field of research in cardiology because of their applicability in the study of the pathogenesis and pathophysiology of this adaptive phenomenon, as well as in the development of novel therapeutic strategies. 13,14 In the literature, most of the existing experimental models that study the effect of increased afterload on left ventricle are based on surgery techniques. Currently, to our knowledge, the available experimental models of pressure overload-induced cardiac hypertrophy include the transverse thoracic aortic banding and the suprarenal abdominal aortic constriction applied usually in small animals like mice, rats and rabbits.…”
Section: Discussionmentioning
confidence: 99%